Classification of anomalous methane fields in the Sea of Okhotsk - Shakirov, Renat B.; Obzhirov, Anatoly I.; Salyuk, Anatoly N.; Biebow, Nicole; Terekhova, Valeriya E.; Tsunogai, Urumu; Shoji, Hitoshi (国立極地研究所, 2005)
An original classification of anomalous methane fields according to the vertical structure of the water column in the Sea of Okhotsk is proposed. Basic types of anomalous methane fields are described: penetrating, near-bottom, deep, intermediate, subsurface, surface, and combined. Anomalous methane concentrations are greater than background values, sometimes by 1-3 orders(up to 30000nl/l above methane hydrates). Spatial and quantitative varieties of anomalous methane fields have genetic relations with different hydrocarbon sources. These varieties suggest a high permeability of active fault zones and geochemical activity in marginal areas, especially along the western Sea of Okhotsk. application/pdf journal article